Pharmacoeconomic Analysis of Heartworm Preventive Compliance and Revenue in Veterinary Practices in the United States - Mwacalimba, Kennedy; Amodie, Deborah; Swisher, Lisa; Moldavchuk, Marina; Brennan, Christopher; Walther, Claire; Bowman, Kelly (Frontiers in Veterinary Science, 2021)
Background: Heartworm disease (HWD) is a fatal condition caused by the nematode Dirofilaria immitis. It is endemic in North America, and the American Heartworm Society recommends that owned dogs be on a Food and Drug Administration approved HWD preventive year-round. The objective of this study was to compare the 12-month HWD preventive purchase compliance rates of injectable moxidectin (ProHeart6®) and the dose equivalent in monthly HWD preventives and their associated economic value to the veterinary hospital. Methods: This study used retrospective anonymized transactional data of 7,926,392 unique dogs from 3,737 companion animal practices across the US for the period 2014–2017. Compliance was defined using American Heartworm Society guidelines. Comparisons were purchases of a 6-month moxidectin injection or 6 doses of any monthly HWD or HWD combination preventive product, tracked for the next preventive purchase 5-7 months later. Total revenue, HWD prevention cost; 12-month repurchase compliance; and patient retention were calculated. Data were summarized in Microsoft Excel™. Compliance comparisons were calculated based on proportion analysis with the SAS ProbNorm function (SAS 9.4, Cary, NC), using a two-sided t-test, at the 5% level of significance (p<0.05). Results: At 51.7%, annual compliance with injectable moxidectin was higher than the dose equivalent in monthly HWD preventives, which was 24.4% (P=0.0001). Eighty-five percent of patients on injectable moxidectin recorded additional transactions during the first visit (average invoice of $161), compared to only 55% of pet owners who purchased monthly HWD prevention (average invoice $141). The average invoice for the first HWD combination product visit was $171, of which $95 was the preventive. The average cost of injectable moxidectin was $48 (29.7% of the total visit invoice; range 28.6%-30.4%). The average cost of 6-doses of HWD prevention was $45 (31.0% of the total invoice; range 30%-32%). Finally, injectable moxidectin dogs had a higher proportion of patients with repeat injections within 12 months between 2014-2017, with 68% retention after 4 years. In comparison, the 6-dose monthly HWD cohort’s retention dropped to 55% by 2017. Conclusions: Injectable moxidectin had better preventive compliance over 12 months and was also associated with better revenue generating potential, and patient retention.